2012
DOI: 10.3354/meps09484
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of increased UV-B and temperature on the pigment-determined marine phytoplankton community of the St. Lawrence Estuary

Abstract: The combined effects of increased UV-B and temperature on natural marine phytoplankton from the St. Lawrence Estuary (Canada) were examined in an 8 d mesocosm experiment carried out in Rimouski (Québec, Canada) in August 2008. We tested the hypothesis that increased temperature (+ 3°C) will offset algal growth suppression by UV-B (78% UV-B increase) using duplicate mesocosm experiments containing natural phytoplankton assemblages. The response of the entire phytoplankton community, in terms of HPLC pigment-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
(66 reference statements)
0
8
1
Order By: Relevance
“…Temperature affects phytoplankton physiology and primary production via biochemical reactions (Cloern 1978). The decrease of micro-sized diatoms observed here contradicts the results of Montagnes & Franklin (2001), who showed that the growth rates of 8 diatom species responded linearly to an increase in temperature (between 9 and 25°C) and the observations of Lionard et al (2012), who reported a positive effect of a 3°C temperature increase on the abundance of diatoms in the St. Lawrence Estuary. Conceivably, diatoms from southern Patagonia, which is a sub-polar ecosystem, are less likely adapted to, and do not benefit from, an increase in temperature.…”
Section: Temperature Effects On the Beagle Channel Microbial Communitycontrasting
confidence: 91%
See 2 more Smart Citations
“…Temperature affects phytoplankton physiology and primary production via biochemical reactions (Cloern 1978). The decrease of micro-sized diatoms observed here contradicts the results of Montagnes & Franklin (2001), who showed that the growth rates of 8 diatom species responded linearly to an increase in temperature (between 9 and 25°C) and the observations of Lionard et al (2012), who reported a positive effect of a 3°C temperature increase on the abundance of diatoms in the St. Lawrence Estuary. Conceivably, diatoms from southern Patagonia, which is a sub-polar ecosystem, are less likely adapted to, and do not benefit from, an increase in temperature.…”
Section: Temperature Effects On the Beagle Channel Microbial Communitycontrasting
confidence: 91%
“…It is also consistent with the studies of Fouilland et al (2013) and Vidussi et al (2011), who observed significant effects of temperature on the abundance and the metabolic rates of the planktonic communities but no synergistic effects of temperature and UVBR. Finally, Lionard et al (2012) also reported a greater effect of temperature than UVBR in structuring phytoplankton communities in the St. Lawrence Estuary. However, as discussed, if our experiment had lasted longer and UVBR effects had become detectable, synergistic or antagonistic effects of temperature and UVBR might have been observed.…”
Section: Uvbr Effects On the Beagle Channel Microbial Communitymentioning
confidence: 82%
See 1 more Smart Citation
“…Higher temperatures decreased the sensitivity to UVR due to the temperature dependence of repair mechanisms. However, Lionard et al [21] did not find any significant effect of temperature or UV-B (280-315 nm) or their interaction, neither on photosynthetic performance nor in diadinoxanthin-based xanthophyll cycle pool size, likely associated to the presence of diatoms, the dominant algal group in the studied communities. This variability in the interactive effects of UVR and temperature on phytoplankton may be partly explained by other factors, such as the optimal temperature range for UVR sensitivity and the capacity of acclimation in each species under different temperatures.…”
Section: Introductionmentioning
confidence: 88%
“…At the organismal level, effects such as decreased growth and photosynthetic rates (Villafañ e et al 2003;Litchman and Neale 2005), changes in morphology , as well as damage to vital cell components such as the deoxyribonucleic acid (DNA) molecule, membrane lipids, and proteins , have been reported due to UVR exposure. At the community level, solar UVR can alter taxonomic composition and size distribution (Lionard et al 2012), potentially affecting trophodynamics, biogeochemical cycles, and the general functioning of the ecosystem.…”
mentioning
confidence: 99%